Ngugi‟sIn the House of the Interpreter: Deconstructing Eurocentric Norms of Writing Memoir by Exposing the Hegemonic Colonial Strategy - Jukkalkar, Syed Imtiaz (International Journal of Psychosocial Rehabilitation, 2020)
Postcolonial writings constructed its identity by deconstructing the Eurocentric norms of literary creation. Memoir as a literary form is an extensionof auto/biography. Auto/biographies were written about the lives of well known men to whom the commons know as heroes. These heroes belong to such societies which are far from the pains of struggle.Therefore the heroes felt an urge to work for either needy or to develop spiritually to guide others and leave behind their contribution for society after their death so that people will remember them at least for a certain period of time.Subvertingthis eurocentric norm, African memoir writing preserves the history of struggle of the society of which the writer is a part, for the future generation. NgugiIn the House of the Interpreterexposes the true face of European hegemonic and the political rise of not an individual but the whole communityfor freedom.